Preparation and characterization of ALKYL-THIOLS monolayer on glass substrates by microcontact printing - Nor Hakimin Abdullah; Wan Azelee Wan Abu Bakar; Rafaqat Hussain; Mohd Bakri Bakar; Mazlan Mohamed; Mohammad Khairul Azhar Abdul Razab; Jan H. Van Esch (2015)
Surface modification is a fascinating method to tailor the surface of material properties such as hydrophilicity, roughness, surface charge and many more. The modification is not only limited to solid materials, but could be possibly extended to particular liquid surfaces. In this paper, surface modification of glass slides with self-assembled monolayers (SAMs) of (3-Mercaptopropyl) trimethoxysilane (MPTMS) was conducted by using a simple method of microcontact printing. Characterizations of the self-assembled monolayer were realized by 3 techniques; (1) Atomic Force Microscopy (AFM) to determine the height of self-assembled monolayer and obtain the topography image, (2) X-ray Photoelectron Spectroscopy (XPS) to further confirm the thiol groups were grafted on the surface and (3) Confocal Fluorescence Microscopy (CFM) to visualize the reaction between thiol terminal groups and fluorescent probe. From the experiment conducted, the result showed that the MPTMS was successfully stamped on glass substrates. AFM scanning images displayed the 0.8±0.2nm height of MPTMS, which matching the size of the MPTS molecules (0.7±0.05nm). XPS spectra indicated the appearance of the doublet structure in the S2p region (S2p3/2 and S2p1/2 levels of the S energy levels) with two peaks in binding energy of 162.8 and 163.8eV respectively. CFM imaging indicated the fluorescent patterns on glass substrates.